2015
DOI: 10.1002/2015gc005977
|View full text |Cite
|
Sign up to set email alerts
|

Phanerozoic surface history of southern Peninsular India from apatite (U‐Th‐Sm)/He data

Abstract: Quantifying bedrock cooling history is crucial for understanding the long‐term landform evolution across passive margins and its control onto the sediment routing system. To constrain the low‐temperature cooling history and its relationships to the Phanerozoic tectonic events of southern Peninsular India, we present new apatite (U‐Th‐Sm)/He (AHe) analyses of 39 Precambrian basement samples. The new AHe ages range from 38.1 ± 6.8 to 364.2 ± 44.6 Ma: they are younger than 50 Ma in the Palghat Gap region and olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 122 publications
(241 reference statements)
0
8
0
Order By: Relevance
“…The sedimentary record of eastern pericratonic basins indicates an increase in sediment accumulation and grain size during the Late Cretaceous–Early Cenozoic (Manmohan et al ., ; Gupta, ; Shanmugam et al ., ), arguably associated with Late Cretaceous climatic shifts triggering drainage reorganization (Mandal et al ., ). The increasing supply of terrigenous detritus has been interpreted to source from the cratonic hinterland (Madhavaraju et al ., ; Bakkiaraj et al ., ).…”
Section: Discussion and Interpretationsmentioning
confidence: 99%
“…The sedimentary record of eastern pericratonic basins indicates an increase in sediment accumulation and grain size during the Late Cretaceous–Early Cenozoic (Manmohan et al ., ; Gupta, ; Shanmugam et al ., ), arguably associated with Late Cretaceous climatic shifts triggering drainage reorganization (Mandal et al ., ). The increasing supply of terrigenous detritus has been interpreted to source from the cratonic hinterland (Madhavaraju et al ., ; Bakkiaraj et al ., ).…”
Section: Discussion and Interpretationsmentioning
confidence: 99%
“…We note that significant Neogene uplift disagrees with the conclusions drawn by Mandal et al . []. Based on the apparent consistency between millennial, 10 Be erosion rates and Cenozoic, AFTA rates, they suggested that the landscape of the southern Indian Peninsula is in steady state (i.e., slow isostatic rebound is balanced by landscape erosion).…”
Section: Drainage Analysismentioning
confidence: 99%
“…It cannot easily be reconciled with 1–1.5 km of denudation following eruption of Deccan basalts that is required to form the Konkan coastal plain. It also disagrees with thermochronologic evidence for significant post‐40 Ma denudation at rates of 60 m Ma −1 across the Kerala‐Konkan lowlands since Late Miocene times [ Kalaswad et al ., ; Gunnell et al ., ; Campanile et al ., ; Mandal et al ., ]. These rates are consistent with cosmogenic nuclide studies and with evidence for ongoing escarpment retreat [ Mandal et al ., , ].…”
Section: Calibration and Testingmentioning
confidence: 99%
See 2 more Smart Citations